Analisis : Kualitas Layanan Omnichannel Terhadap Loyalitas Pelanggan di Era Digital (Study Kasus Pada PT. Angbar Express Samjaya, Kota Bandung) - Osama Muhammad Afganis; Ooy Siti Halimah (KarismaPro, 2025)
This study aims to examine the quality of omnichannel services and their role in building customer loyalty in the digital era at PT Angbar Express Samjaya, a company operating in freight transportation, car rental, and tour and travel services. This research adopts a qualitative method using a case study approach. Data were collected through in-depth interviews, direct observation, and documentation involving company management and customers. The findings reveal that the implementation of integrated, consistent, and responsive omnichannel services plays a significant role in enhancing customer satisfaction and fostering long-term loyalty. Customers perceive greater convenience and flexibility when accessing services through multiple channels, both online and offline, which contributes to a more seamless service experience. Furthermore, the integration of digital and conventional service channels strengthens customer trust and engagement with the company. This study highlights that omnichannel service quality is not only a supporting operational tool but also a strategic asset in maintaining competitiveness in the digital era. The results imply that transportation service companies should continuously develop and optimize omnichannel strategies to improve service effectiveness, meet evolving customer expectations, and sustain customer loyalty amid increasingly intense market competition.